Pectin emulsions for colon-targeted release of propionic acid. (June 2020) - Du Le, Hoang; Loveday, Simon M.; Nowak, Emilia; Niu, Zhigao; Singh, Harjinder
Abstract: In this study, we aimed to design emulsion system, using pectin as an emulsifier that could resist gastric and intestinal digestion, and deliver tripropionin (glyceryl tripropionate) as propionic acid precursor to the colon. The stability and the degree of lipolysis of the emulsions under in vitro gastrointestinal digestion were assessed using droplet sizing, microscopy, ζ-potential and quantification of tripropionin, propionic acid and pectin coverage. The emulsions were stable in the gastric stage, and the stability under intestinal conditions was dependent on the concentration of pectin. The microscopic structure demonstrated a certain degree of coalescence of all emulsions after intestinal digestion, with the most affected emulsion being that at the lowest pectin concentration. Pectin concentrations of ≥2.5 wt% improved the resistance of the emulsion to coalescence and reduced the rate of lipolysis and the degree of hydrolysis, all of which were due to thicker pectin coverage. This apparently improved the resistance to displacement by bile salts and the subsequent adsorption of colipase and lipase that occur in the initial phase of lipid digestion. The use of pectin to form gastrointestinal-resistant emulsions is a promising approach to delaying the digestion of tripropionin, or other lipid-based materials, and to deliver tripropionin to the colon. Graphical abstract: Image 1 Highlights: Emulsions stabilised by citrus pectin were stable in the gastric stage. Emulsion stability in the intestinal stage was dependent on pectin concentration. Pectin concentrations of ≥2.5 wt% significantly reduced the lipolysis rate. Reduction in the lipolysis rate was due to thicker pectin coverage. Thick pectin coverage delays digestion by interfering with bile salt displacement.